Aspartame-Triggered Migraine - J Gordon Millichap (Pediatric Neurology Briefs)
Two patients with known aspartame-triggered and rizatriptan-responsive migraine had their headaches worsened following use of an aspartame-containing formulation of rizatriptan (Maxalt-MLT), in a report from Albert Einstein College of Medicine, Bronx, NY.